Analyzing the relationships between nursing students' academic performance, academic procrastination, burnout, and GPA - Syiddatul Budury; Mei Nanda Sampurno; Nunik Purwanti; Diah Jerita Eka Sari; Siti Khuzaimah Ahmad Sharoni (Faculty of Nursing Universitas Padjadjaran, 2026)
Background: The current learning system, which employs hybrid learning methods, requires students to adapt and manage their time effectively. Failure to do so may increase the risk of experiencing academic burnout and procrastination. Purpose: This study aims to explore the relationship between academic burnout, academic procrastination, self-regulated learning, academic performance, and Grade Point Average (GPA) among students. Methods: A cross-sectional study was conducted with 310 nursing students selected through purposive sampling. The variables examined were academic burnout, academic procrastination, self-regulated learning, academic performance, and GPA. The instruments used included the Self-Regulated Learning Scales, the Maslach Burnout Inventory Student Survey, the Active Procrastination Scale, and the Academic Performance Scale. Statistical analysis was performed using Structural Equation Modeling (SEM) with Partial Least Squares (PLS). Results: The confirmatory factor analysis of the scales indicated that SRMR=0.125, NFI=0.620, and RMS theta=0.190, suggesting that the model does not meet the criteria for a good fit. The R-square value was 0.481, indicating that self-regulated learning, academic procrastination, and burnout collectively influence academic performance. Conclusions: These findings contribute to the literature by highlighting the role of self-regulated learning and procrastination in academic outcomes while calling into question the reliability of GPA as a sole indicator of academic success.